Design of photonic rearrangeable networks with zero first-order switching-element-crosstalk. - Maier, G. (IEEE Transactions on communications)
The development of optical cross-connect architectures is a very important topic today. We consider here in particular the class of optical space-division switching fabrics configured as multistage structures built with 2×2 optical switching elements (SEs) and derived from a combination of vertical replication and horizontal expansion of Banyan networks. We determine the necessary and sufficient conditions for these matrices to be rearrangeably nonblocking and free of first-order crosstalk in SEs. This impairment is one of the major limitations in optical cross-connect performance. We focus on rearrangeable matrices since they have lower complexity than their strict-sense nonblocking counterparts. Given the current high cost of optical SEs, the rearrangeable solution looks attractive today